DFT investigation of carbon dioxide effects with temperature on hydrated tetra and penta-saccharide complexes - Bamba, EL Hadji Sawaliho; N’Guessan, Boka Robert; Ablé, Anoh Valentin (European Journal of Applied Sciences, 2021)
Plantain banana mainly constitutes by water and starch. The latter includes amylopectin and amylose. Glucose represents their core molecule. This work aims to elucidate the temperature and carbon dioxide effects in four (AM4G) or five (AM5G) of its hydrated synthons (basic unit). Ultimately, it wants to identify their role in the deterioration of starch components. The research exploits the resources of quantum chemistry to generate the relevant geometric, thermodynamic, and spectroscopic parameters related to the hydrated tetra and penta-saccharide at the ONIOM level (B3LYP/6–311++G [d, p]: AM1). Their analysis reveals the following results. The temperature maintains the geometries of both complexes. It retains most of the enthalpies, and entropy associated with their formation. Moreover, it lowers the free enthalpies of the latter. Furthermore, it increases the frequency shifts . This work also identifies the action of carbon dioxide. This one almost conserves the geometry of the two complexes and their hydrogen bonds. Its effects on the thermodynamic quantities depend on the temperature. Carbon dioxide maintains the exothermic character of the complexations involved. More, it transforms their entropy. It increases the free enthalpy of fluctuating importance. It keeps the non-spontaneity of complexation reactions. Its effects concern the frequency shifts . These rely on the temperature. Dioxide carbon exalts them in function of these latter.